ANALISIS PENGARUH DIVERSIFIKASI PRODUK ELEKTRONIK TERHADAP MINAT BELI ULANG DENGAN REPUTASI PERUSAHAAN SEBAGAI VARIABEL MODERATOR PADA UD. SABAR MENANTI DI GERUNG LOMBOK BARAT - Mina Novianty Eka Lavionita (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
The bad economic conditions make competition in the business world becomes more intense,so that this makes employers continuously improve their efforts to achieve company goals.In order to achieve the goal, the company needs to try some marketing strategies such asproduct diversification, because the product diversification can increase consumerrepurchase interest. To maintain the the interest, the company must also pay attention to thecompany's reputation as what has been done by UD Sabar Menanti to survive in theelectronic market in Gerung while competitors retreated. This study is aimed at analyzingthe significant effect of the variables of product diversification and of the variables ofcompany reputation on the repurchase interest at UD Sabar Menanti in Gerung WestLombok. This research is associative research. Data are collected through a sample surveywith purposive sampling technique of 100 respondents. Data are collected throughobservation, interview and a questionnaire. Data analysis method used is the structuralanalysis equation modelling with LISREL program version 8.80. The first estimation showedthat diversification of electronic products significantly affect direct repurchase interest. Thesecond estimation indicated that both variables of product diversification and companyreputation and the interaction did not significantly affect the repurchase interest. Thus it isconcluded that product diversification variable positively and significantly affect therepurchase interest. While the variable of company reputation did not affect the therepurchase interest and could not moderate the relation between the company reputationand the repurchase interest in UD Sabar Menanti in Gerung West Lombok. It is suggested,then, that UD Sabar Menanti continue to develop product diversification in order toincrease the repurchase interest.Keywords: product diversification, company reputation, repurchase interest.